Transcranial Direct Current Stimulation Modulates Neurogenesis and Microglia Activation in the Mouse Brain - Anton Pikhovych; Nina Paloma Stolberg; Lea Jessica Flitsch; Helene Luise Walter; Rudolf Graf; Gereon Rudolf Fink; Michael Schroeter; Maria Adele Rueger (Stem Cells International)
Transcranial direct current stimulation (tDCS) has been suggested as an adjuvant tool to promote recovery of function after stroke, but the mechanisms of its action to date remain poorly understood. Moreover, studies aimed at unraveling those mechanisms have essentially been limited to the rat, where tDCS activates resident microglia as well as endogenous neural stem cells. Here we studied the effects of tDCS on microglia activation and neurogenesis in the mouse brain. Male wild-type mice were subjected to multisession tDCS of either anodal or cathodal polarity; sham-stimulated mice served as control. Activated microglia in the cerebral cortex and neuroblasts generated in the subventricular zone as the major neural stem cell niche were assessed immunohistochemically. Multisession tDCS at a sublesional charge density led to a polarity-dependent downregulation of the constitutive expression of Iba1 by microglia in the mouse cortex. In contrast, both anodal and, to an even greater extent, cathodal tDCS induced neurogenesis from the subventricular zone. Data suggest that tDCS elicits its action through multifacetted mechanisms, including immunomodulation and neurogenesis, and thus support the idea of using tDCS to induce regeneration and to promote recovery of function. Furthermore, data suggest that the effects of tDCS may be animal- and polarity-specific.